Epitranscriptomics of SARS-CoV-2 Infection - Izadpanah, Amin; Rappaport, Jay; Datta, Prasun K. (Frontiers in Cell and Developmental Biology, 2022)
Recent studies on the epitranscriptomic code of SARS-CoV-2 infection have discovered various RNA modifications, such as N6-methyladenosine (m6A), pseudouridine (Ψ), and 2′-O-methylation (Nm). The effects of RNA modification on SARS-CoV-2 replication and the enzymes involved in this mechanism are emerging. In this review, we summarize the advances in this emerging field and discuss the role of various players such as readers, writers, and erasers in m6A RNA methylation, the role of pseudouridine synthase 1 and 7 in epitranscriptomic modification Ψ, an isomer of uridine, and role of nsp16/nsp10 heterodimer in 2'-O-methylation of the ribose sugar of the first nucleotide of SARS-CoV-2 mRNA. We also discuss RNA expression levels of various enzymes involved in RNA modifications in lung tissues of SARS-CoV-2 infected individuals and their impact on host mRNA modification. In conclusion, these observations will facilitate the development of novel strategies and therapeutics for targeting RNA modification of SARS-CoV-2 RNA to control SARS-CoV-2 infection.